Delivering on the National Planning Framework - Hogan, Paul (Statistical and Social Inquiry Society of Ireland, 2018)
The National Planning Framework (NPF) was published by Government together with the National Development Plan, as ‘Project Ireland 2040’, in February 2018. An explanation of how the National Planning Framework will be implemented, is assisted by setting out the overall context for planning in Ireland, as well as the spatial pattern of settlement in recent decades. It is in this context that the logic and intent of the NPF strategy and the necessary levers for implementation, become apparent.
read before the Society, 26 April 2018; Symposium: ‘Where’ will the Economy be in 2040? Delivering on the National Development Framework
Keywords: 314.15